ANALISIS IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PEMBERDAYAAN MASYARAKAT PADA PT. PERKEBUNAN NUSANTARA IV SOSA DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Aminah Lubis; Saparuddin Siregar; Isnaini Harahap (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
This study aims to analyze in depth about: 1) The Partnership and Community Development program of PT. Perkebunan Nusantara IV Sosa, 2) The Implementation of Corporate Social Responsibility (CSR) PT. Perkebunan Nusantara IV Sosa in Community Empowerment, and 3) Review of Shariah Enterprise Theory (SET) to the Corporate Social Responsibility Program (CSR) at PT. Perkebunan Nusantara IV Sosa. This research is a field research with descriptive in qualitative research-inductive. The subjects were community and employees of PTPN IV Sosa. The primary data obtained through interviews with community and employee PTPN IV Sosa. The results showed that the Corporate Social Responsibility Program (CSR) PTPN IV-Sosa has implemented: (1) The provision of venture capital loan fund, grants; (2) Education (providing scholarships and improve school buildings); (3) Spiritual (repair houses of worship); (4) Infrastructure or public facilities (repairing roads and help provide school equipment); (5) The health sector (provision of funds for the provision of basic needs of natural disasters, drug, mass circumcision); and (6) Nature conservation (reforestation).  Implementation of CSR programs PTPN IV Sosa channeled properly, for the partners held training and as expected by the public. Loking from the purposes, the implementation of the Enterprise  Theory Shariah of the Corporate Social Responsibility (CSR) PTPN IV-Sosa has been in accordance with the principle of fair share, maslahah and rahmatan lil'alamῑn